PROGRAM EDUKASI ANAK CERDAS DI ERA DIGITAL DALAM MEMBANGUN LITERASI DAN NUMERASI MELALUI PEMANFAATAN TEKNOLOGI DI SD NEGERI 5 BHUANA GIRI - I Made Sujana Adnyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This community service program aims to enhance elementary school students’ literacy and numeracy skills through the utilization of digital technology. The program was implemented at SD Negeri 5 Bhuana Giri under the theme “Smart Kids in the Digital Era” as an effort to foster intelligence, creativity, and 21st-century skills among young learners. The rapid advancement of technology requires students not only to be literate in reading and numeracy but also to possess digital literacy in order to adapt to modern learning environments. The implementation methods included socialization, interactive training, and mentoring sessions on the use of digital learning media and applications focused on literacy and numeracy. Students were introduced to various digital learning tools such as educational games, interactive videos, and engaging numeracy applications to increase their learning motivation. Teachers were also involved to ensure the sustainability of technology integration in classroom activities. The results of the program indicated an increase in students’ enthusiasm for learning, better understanding of basic literacy and numeracy concepts, and improved ability to use digital devices responsibly and effectively. Through this program, students of SD Negeri 5 Bhuana Giri are expected to become intelligent, creative, and adaptive individuals in facing technological advancements. Moreover, this initiative serves as a practical example of how basic education can synergize with technological innovation to build a strong foundation of digital intelligence from an early age.